Secure System Design and Trustable Computing - Chang, Chip-Hong.; Potkonjak, Miodrag; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides the foundations for understanding hardware security and trust, which have become major concerns for national security over the past decade.  Coverage includes issues related to security and trust in a variety of electronic devices and systems related to the security of hardware, firmware and software, spanning system applications, online transactions, and networking services.  This serves as an invaluable reference to the state-of-the-art research that is of critical significance to the security of, and trust in, modern society's microelectronic-supported infrastructures.
Part I : Hardware Security Primitives -- Disorder-Based Security Hardware: An Overview -- Design and Implementation of High-Quality Physical Unclonable Functions for Hardware-oriented Cryptography -- Digital Bimodal Functions and Digital Physical Unclonable Functions: Architecture and Applications -- Residue number systems in cryptography: design, challenges, robustness -- Fault Attacks on AES and their Countermeasures -- Hardware Counterfeiting and Integrity Protection -- Circuit Timing Signature (CTS) for Detection of Counterfeit Integrated Circuits -- Hardware Trojan Detection in Analog/RF Integrated Circuits FPGAs -- Obfuscation-based Secure SoC Design for Protection against Piracy and Trojan Attacks -- Towards Building Trusted Systems: Vulnerabilities, Threats and Mitigation Techniques -- Hardware IP Watermarking and Fingerprinting.
Keywords: Electronic circuits; Data protection; Electronics; Electronic Circuits and Systems; Data and Information Security; Electronics and Microelectronics, Instrumentation